IND.216: a phase II study of buparlisib and associated biomarkers, raptor and p70S6K, in patients with relapsed and refractory chronic lymphocytic leukemia. Issue 7 (6th June 2020) - Assouline, Sarit; Amrein, Lilian; Aloyz, Raquel; Banerji, Versha; Caplan, Stephen; Owen, Carolyn; Hasegawa, Wanda; Robinson, Sue; Shivakumar, Sudeep; Prica, Anca; Peters, Anthea; Hagerman, Linda; et al.
Abstract: Buparlisib is an orally available pan-Class I PI3K inhibitor, that is more potent than idelalisib in vitro . Its distinct toxicities include hyperglycemia, hypertension, and mood disturbance. IND216 is a single arm phase II trial of buparlisib in Relapsed/refractory (R/R) chronic lymphocytic leukemia (CLL). Fourteen patients were enrolled, 13 were evaluable for response and toxicity. Six of 13 patients had a partial response (46%) with a median duration of response of 15.5 months, all 11 patients with tumor assessment experienced tumor shrinkage. The most common adverse events (≥15%) were hyperglycemia, fatigue, anxiety, and gastrointestinal toxicities; all were < grade 3 except for fatigue. Three patients stopped therapy for alterations in mood. Lower levels of raptor were significantly associated with greater tumor shrinkage, suggesting that raptor could be a biomarker for response. This requires further validation in a larger CLL patient cohort. The clinical activity of buparlisib is comparable to other phosphatidylinositol-3-kinase inhibitors, with a different toxicity profile. Novelty and impact: Buparlisib, an oral, pan PI3 kinase inhibitor, is associated with a 46% partial response rate among patients with relapse chronic lymphocytic leukemia (CLL). This is a similar clinical activity to other phosphatidylinositol-3-kinase inhibitors tested. However, buparlisib has a distinct toxicity profile, characterized by hyperglycemia, hypertension, and mood alteration. In agreement with our previous preclinical study, our results suggest that basal raptor expression in CLL correlates with clinical response to buparlisib.